PENERAPAN TEKNOLOGI TINGGI UNTUK PENGELOLAAN LIMBAH PADAT DI SINGAPURA - Sri Wahyono (Jurnal Teknologi Lingkungan, 2004)
The application of high technology (hitech) for solid waste management andtreatment in Singapore is one of examples of solving the municipal solid waste problem. Singapore with more than 4 million inhabitants produced 7676 ton wastes per day in 2001. Now, all the combustible solid wastes goes to the incinerator plant that can convert the heat into electricity. The ash from incinerator and the incombustible solid wastes are transported via waste harbour in Tuas to the Semakau off shore landfill. Also, before incinerating in the plant, the activities of collecting and transporting of munocipal solid wastes are suported by such kind of new technologies for example pneumatic refuse transport system. The typical of the high tecnology is need high cost for building, operating and maintaining and should be operated by high skill staff. Singapore has all the need and also has a strong political will in combating the solid waste problems. So that, Singapore is one of the cleanest metropolitan cities in the world.